Temporal Variations of Water Discharge and Sediment Load of Huanghe River, China - Liu, Feng; Chen, Shenliang; Peng, Jun; Chen, Guangquan (Chinese geographical science, 2012)
Based on the data from gauging stations, the changes in water discharge and sediment load of the Huanghe （Yellow） River were analyzed by using the empirical mode decomposition （EMD） method. The results show that the periodic oscillation of water discharge and sediment load of the Huanghe River occurs at the interannual, decadal, and multi-decadal scales, caused by the periodic oscillations of precipitation, and E1 Nifio/Southern Oscillation （ENSO） af- fects water discharge by influencing precipitation distribution and contributes to periodic varations in precipitation and water discharge at interannual timescale. The water discharge and sediment load of the Huanghe River have decreased since the 1960s under the influence of precipitation and huamn activities, and human activities attribute more than precipitation to the reduction in the water discharge and sediment load, furthermore, water abstraction and water-soil conservation practices are the main causes of the decrease in water discharge and sediment load, respectively. The reduction in sediment load has directly impacted on the lower reaches of the Huanghe River and the river delta, causing considerable erosion of the river channel in the lower reaches since the 1970s along with River Delta changing siltation into erosion around 2000.